Recent advances of NIR-TADF (λmaxPL/EL > 700 nm) emitters and their applications in OLEDs. Issue 42 (18th October 2022) - Sharma, Simran; Pal, Amlan K.
Abstract : This review presents a new vista on the recent advances in molecular design, photophysical and electroluminescence performances of NIR emitters and their OLEDs. Abstract : The rise of organic thermally activated delayed fluorescence (TADF) materials as NIR emitters and hosts have engrossed wide consideration as they can demonstrate 100% internal quantum efficiency. These materials have exceeded the phosphorescent noble-metal complexes due to cost-efficiency without compromising the OLED performance. Numerous applications of the NIR spectrum, e.g., in telecommunication, night-vision display, biomedical applications, and chemical sensors, render the NIR-TADF emitters vulnerable to evolution. This review highlights the various strategies adopted in the recent past (2015–2022) to judiciously design purely organic NIR-TADF emitters ( λ maxPL/EL > 700 nm) with in-depth discussions of photophysical and device-electroluminescence studies. Approaches such as the incorporation of extended π-conjugated acceptors, diazoles of group-16 elements, 'BF2 '-acceptor, non-conjugated donor–acceptor dendrons, exciplex formation, and TADF sensitization provide effective pathways to construct high-efficiency NIR-TADF-OLEDs. Thus, this review aims to provide a new perspective for the next generation researchers to implement strategies for the thoughtful design of efficient NIR-TADF materials.